Laboratory manual in elecricity-electronics fundamentals - Bosita, Gil ([Place of publication not identified] : [Publisher not indicated[, 1996)
This manual is written to provide hands-on exercises for verification and realization of some principles in basic electricity and electronics. Technicians or engineering students in any electronic-related course can use this manual.
Keywords: ELECTRICITY -- HANDBOOKS AND MANUALS; ELECTRONICS -- HANDBOOKS AND MANUALS